Root-Colonizing Endophytic Fungi of the Dominant Grass Stipa krylovii From a Mongolian Steppe Grassland - Knapp, Dániel G.; Imrefi, Ildikó; Boldpurev, Enkhtuul; Csíkos, Sándor; Akhmetova, Galiya; Berek-Nagy, Péter János; Otgonsuren, Burenjargal; Kovács, Gábor M. (Frontiers in Microbiology, 2019)
In several terrestrial ecosystems such as grasslands, plants live together with various root colonizing dark septate endophytes (DSE), fungi that are relatively frequent colonizers of healthy belowground tissues of plants in these environments. They are important members of the plant microbiota and may have various effects on plant survival under different stress conditions; however, their general functions in relation to plants and the greater ecosystem remain elusive. Although, an increasing number of studies has been published focusing on DSEs in Asian grasslands, our knowledge is limited. Especially in Mongolia, where the steppe region represents a significant area, information is not available on these root colonizers. In this study, we aimed to characterize DSEs of a common dominant gramineous plant species, Stipa krylovii in a semiarid grassland of Mongolia. Root samples were collected in a natural steppe and were processed for isolation of fungal endophytes. For molecular identification of the isolates, the internal transcribed spacer (ITS) region of the nrDNA was obtained for all the isolates investigated; furthermore, the partial translation elongation factor 1-α (TEF) gene, and large subunit (LSU) and small subunit (SSU) of rDNA were also amplified and sequenced in case of representative isolates. In vitro tests were used to examine the rough symbiotic nature of the fungi, and root colonization was visualized. A majority of the 135 isolates examined in detail was found to belong to several orders of Ascomycota (110 isolates) and some to Basidiomycota (25 isolates). A significant number of the isolates represented presumably novel taxa, and dominant similarities of the lineages have been found with relatively frequent and known grass root endophytes of semiarid areas in other geographic regions. These endophytes included Periconia macrospinosa, Microdochium bolley and Darksidea, the genus of which comprised one fourth of the isolates. We found numerous lineages, which have been detected not only from Asian steppe ecosystems, but also from prairies in North America and sandy grasslands in Europe. Therefore, our results strengthen the hypothesized worldwide presence of a common and dominant core group of a DSE community in arid and semiarid grasslands.